Effect of estrous cycle phase on vulvar, orbital area and muzzle surface temperatures as determined using digital infrared thermography in buffalo - de Ruediger, Felipe Rydygier [UNESP] (2018)
The objective of this study was to evaluate variations in the orbital area, muzzle and vulva surface temperatures and progesterone (P4) concentrations during follicular and luteal phases in Murrah buffalo and whether these temperatures are influenced by the weather patterns. Forty cows were submitted to P4-based hormonal protocol. After P4 device withdrawal transrectal ultrasonography and infrared digital thermography were performed daily until day 16 and on days 20, 24, 28 and 32 to follow the ovulation as well as the vulva, orbital area and muzzle temperatures. In addition, the weather variables were evaluated, as well as rectal temperature (RT) and P4 and cortisol concentration. Vulva, muzzle and orbital area temperatures correlated positively with RT and with weather data. Greater temperatures of the vulva, orbital area and muzzle were detected during the period of estrus. The vulvar surface temperature (VST) was not influenced to a great extent by weather factors during the morning, so this period was chosen to evaluate the influence of the phase of the estrous cycle on VST. The VST was less during days 16, 20, 24 and 28 (diestrus) and P4 concentration was inversely proportional to the VST. Muzzle, orbital area and RT, however, were not of the same pattern. Negative correlations were observed between VST and P4 concentrations. It is concluded that VST undergoes changes during the reproductive phases, correlating with P4 concentration. The weather factors influence the temperatures of the body surface areas, and the morning is the most desirable time to perform the thermographies.